Persepsi dan Produksi Tuturan BIPA Penutur Jati Bahasa Inggris - Faisal Azhar (Jurnal Bahasa Indonesia bagi Penutur Asing, 2020)
Speakers of two or more languages or known as multilinguist who could produce speech yet differently from their perception. A language which used outside their social context generally known as foreign language. The Ministry of Education and Culture of the Republic of Indonesia has since 2017 held a program titled Apresiasi PemenangLomba Berpidato dan Bercerita (APLBB BIPA) which awardees are from around the globe. In 2019, the awardees were the winner of speech and story-telling competition in Indonesian Embassies and Consulates from twenty-one countries, including the L1 English-speaker from Australia, and the United States of America. L2 speakers often produce different speech than they have perceived, in this case, with the awardees of APLBB BIPA L1 English-speakers. Based on perception and speech production analysis, it is found that phonological variables such as vocals, consonants, and sound-added vocals produced by L1 English-speaker awardees appeared. This means that they perceived the sounds differently from their speech productions